Subtle Europeanisers: Czech and Slovak advocacy and assistance strategy in the Western Balkans - Hronešová, J (Routledge, 2015)
Two and half decades after the fall of the Berlin Wall, Europe has made signifi cant headway in unifi cation “despite its diversity”. In unprecedented “big bang” rounds of EU enlargement, eight Central and East European (CEE) countries joined the European Union in 2004; two Eastern Balkan countries, Bulgaria and Romania, in 2007; and the fi rst Western Balkan country, Croatia, became the EU’s 28th member state in July 2013. As of early 2015, the rest of the Western Balkans (WB) 2 has obtained either a candidate status (Albania, the Former Yugoslav Republic of Macedonia-FYROM, Montenegro and Serbia) or a potential candidate status (Bosnia and Herzegovina and Kosovo).